Crowding-in or crowding-out: the contribution of self-determination theory to public service motivation. Issue 7 (2nd July 2020) - Corduneanu, Roxana; Dudau, Adina; Kominis, Georgios
ABSTRACT: The relationship between monetary rewards and public service motivation (PSM) has been at the centre of public management research for several decades. Yet the role of performance-contingent rewards in motivating individuals to engage in public service behaviour remains largely contested. This conceptual study aims to reconcile inconsistencies in the literature by considering particular conditions under which performance-contingent incentives may effectively sustain PSM. Drawing on self-determination theory, this study offers a detailed map of the factors that can explain the relationship between performance-related rewards and PSM, while also reconciling contradictory research findings to date and making several propositions for empirical research.